2019
DOI: 10.1186/s12913-019-4640-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a predictive model for American Society of Anesthesiologists Physical Status

Abstract: BackgroundThe American Society of Anesthesiologists Physical Status (ASA-PS) classification system was developed to categorize the fitness of patients before surgery. Increasingly, the ASA-PS has been applied to other uses including justification of inpatient admission. Our objectives were to develop and cross-validate a statistical model for predicting ASA-PS; and 2) assess the concurrent and predictive validity of the model by assessing associations between model-derived ASA-PS, observed ASA-PS, and a divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…We evaluated descriptive and radiographic data, including age, sex, body mass index, American Society of Anesthesiologists grade, 28 pre- and postoperative hip-knee-ankle angle, pre- and postoperative WBL ratio, severity of OA with Kellgren-Lawrence (KL) grade, 21 and preoperative cartilage grade of the medial femoral condyle and medial tibial condyle during arthroscopic examination with the ICRS (International Cartilage Regeneration and Joint Preservation Society) classification. 18 The radiographic assessment was based on weightbearing full-length hip-to-ankle radiographs.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated descriptive and radiographic data, including age, sex, body mass index, American Society of Anesthesiologists grade, 28 pre- and postoperative hip-knee-ankle angle, pre- and postoperative WBL ratio, severity of OA with Kellgren-Lawrence (KL) grade, 21 and preoperative cartilage grade of the medial femoral condyle and medial tibial condyle during arthroscopic examination with the ICRS (International Cartilage Regeneration and Joint Preservation Society) classification. 18 The radiographic assessment was based on weightbearing full-length hip-to-ankle radiographs.…”
Section: Methodsmentioning
confidence: 99%
“…Forty pet dogs affected by OA were referred by the Veterinary Teaching Hospital of the University of Camerino and enrolled in the study with their owners’ consent. Eligibility criteria included dogs aged 1 to 15 years, with no weight and sex restriction, belonging to the ASA 1–2 anesthetic risk class [ 38 ]; absent of comorbidity, pregnancy, or lactation; affected by lameness manifesting in one joint caused by OA; absent of OA in other joints of the same limb; belonging to radiographic grade OA between 1 and 4 (according to a modified Kellgren-Lawrence scale) [ 39 ]; and having not received anti-inflammatory drugs nor nutraceuticals in the 15 days prior to enrollment in the study. The entire cohort of patients who concluded the study had to follow a management therapy after receiving the treatment, limiting uncontrolled activities, favoring leashed walks, and avoiding nutraceuticals or anti-inflammatory drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in vivo studies have also reported interesting results, despite having their limits [ 33 , 34 ]. Over the past decade, research has brought new insights into the effects of ASCs, and new mechanical disintegration technologies promise rapid, ready-to- use stem cell collection under the principle of “minimum manipulation” [ 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the underlying comorbidities was assessed using the Charlson Comorbidity Index (CCI) [ 30 ]. The American Society of Anesthesiologists classification (ASA) was used to estimate the patient's preoperative risk [ 31 ]. Preoperative levels of albumin, leukocytes, platelets, hemoglobin and C-reactive protein (CRP) were obtained from the patients’ medical records.…”
Section: Methodsmentioning
confidence: 99%